English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

this problem has been bugging me for the last 25 minutes


Solve. If no solution exists say NO SOLUTION

10/y^2 - 4 = 1 - 1/y + 2

appreciate the help

2007-01-07 15:23:04 · 7 answers · asked by brett y 1 in Science & Mathematics Mathematics

ya sorry its 1/(y+2)

2007-01-07 16:30:38 · update #1

7 answers

10/y^2 - 4 = 1 - 1/(y + 2 ) ?

It's hard to read your question.
---------------
I guess it is

10/(y^2-4) = 1 - 1/(y+2)

If it is true, then
10/[(y+2)(y-2)] = (y+1)/(y+2)

Multiply by (y+2),
10/(y-2) = y+1
which is equivalent to
10 = y^2-y-2
y^2-y-12 = (y+3)(y-4) = 0

y = -3, or 4

2007-01-07 15:26:45 · answer #1 · answered by sahsjing 7 · 0 1

If I am reading this right it is

10/(y^2-4) = 1 - 1/(y+2)

Factor the y^2-4 into (y+2)(y-2) and mutiply both sides by (y+2)(y-2) which is the least common denominator

[10(y+2)(y-2)/(y+2)(y-2)] = 1*(y+2)(y-2) - [1(y+2)(y-2)/(y+2)]

Now cancel where you can and this simplifies to

10 = (y+2)(y-2) - (y-2)
10 = y^2 - 4 - y + 2
10 = y^2 - y - 2
y^2 - y - 12 = 0
(y+3)(y-4) = 0
y = -3, 4

** be sure to check that your solutions are within the domain of the problem!!

2007-01-07 23:34:51 · answer #2 · answered by hunneebee22 4 · 1 0

10 / (y^2 - 4) = 1 - 1/(y+2) ==> Multiply both sides by y+2, noting that (y^2 - 4) = (y+2)(y-2)
10 / (y-2) = y+2-1 = y+1 ==> Multiply both sides by y-2
10 = (y+1)(y-2) = y^2 - y - 2
0 = y^2 - y - 12
0 = (y+3)(y-4)
y = -3 or y = 4

2007-01-07 23:33:14 · answer #3 · answered by Anonymous · 0 0

10/y^2 - 4 = 1 - 1/y + 2
Multiplying both sides by y^2
10 - 4y^2 = y^2 - y + 2y^2
0 = - 10 + 4y^2 + y^2 - y + 2y^2 = 7y^2 - y - 10
7y^2 - y - 10 = 0
y = [1 +- sqrt{1^2 - 4(7)(-10)}] / [2(7)]
y = [1 +- sqrt281] / 14 = [1 +- 16.8] / 14
y = 1.27 and y = 1.13

2007-01-07 23:34:20 · answer #4 · answered by Sheen 4 · 0 1

10/(y-2)(y+2)=1- 1/(y+2)
10/(y-2)= (y+2) -1
10/(y-2)=(y+1)
10=(y+1)(y-2)
10=y^2-y-2
0=y^2-y-12
0=(y-4)(y+3)
y=4 or -3

2007-01-07 23:33:22 · answer #5 · answered by thomas 7 · 0 1

add 4 to both sides

10/y^2=7+1/y

subtract 1/y from both sides

10/y^2-1/y=7

multiply 1/y by y/y

10/y^2-y/y^2=7

combine fractions

(10-y)/y^2=7

multiply both sides by y^2

10-y=7y^2

rearrange

7y^2+y-10=0

use quadratic formula

y=(-1+/-(1+280)^.5)/14

solve the rest yourself :-)


I think i ready your problem wrong though, you really need to use parenthesis

2007-01-07 23:34:21 · answer #6 · answered by Anonymous · 0 1

Your question is ambiguous. Please use parentheses to eliminate ambiguity and restate it so we can answer.

2007-01-07 23:30:40 · answer #7 · answered by Northstar 7 · 0 1

fedest.com, questions and answers